2018
DOI: 10.7567/apex.11.031301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of RF power on the properties of intrinsic hydrogenated amorphous silicon passivation layer deposited by facing target sputtering

Abstract: We demonstrated the deposition of high-quality intrinsic hydrogenated amorphous silicon (i-a-Si:H) passivation layers for silicon heterojunction (SHJ) solar cells by facing target sputtering (FTS). The RF power of FTS significantly affects the electrical properties of i-a-Si:H and the passivation quality at the i-a-Si:H/crystalline silicon interface. A low surface recombination velocity of 7.0 cm/s and a relatively high deposition rate of 4.0 nm/min were simultaneously achieved at the optimum RF power. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In our previous publications, we reported the deposition of amorphous silicon by FTS under low sputtering damage conditions. [17][18][19] FTS employs two facing sputtering targets, and the plasma is confined between the targets. This results in very low sputtering damage to the c-Si wafer.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous publications, we reported the deposition of amorphous silicon by FTS under low sputtering damage conditions. [17][18][19] FTS employs two facing sputtering targets, and the plasma is confined between the targets. This results in very low sputtering damage to the c-Si wafer.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, we have obtained a relationship among hydrogen composition, substrate temperature, optical characteristics, and thermal durability. However, previous research in the field of solar cells has reported that the carrier lifetime of a-Si:H produced by sputtering tends to decrease owing to the plasma damage of high-energy particles [9,10]. Therefore, damage reduction by facing target sputtering (FTS), which separates the substrate from the charged particle space, is being investigated [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous research in the field of solar cells has reported that the carrier lifetime of a-Si:H produced by sputtering tends to decrease owing to the plasma damage of high-energy particles [9,10]. Therefore, damage reduction by facing target sputtering (FTS), which separates the substrate from the charged particle space, is being investigated [10]. However, no research has been conducted on the effects of plasma damage on a-Si:H in optical film applications.…”
Section: Introductionmentioning
confidence: 99%
“…Sputter deposition has been one of the most widely adopted thin-film deposition techniques due to advantages like largearea homogeneous film deposition, no involvement of hazardous gases, and a relatively low-cost process. A few research groups have reported the application of sputter-deposited intrinsic a-Si:H (S-i-a-Si:H) layers for c-Si surface passivation [7][8][9]. Zhang et al [8] demonstrated c-Si surface passivation by S-i-a-Si:H layers, and highlighted the c-Si surface damage during the sputtering process.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [8] demonstrated c-Si surface passivation by S-i-a-Si:H layers, and highlighted the c-Si surface damage during the sputtering process. Shiratori et al [9] adopted a facing target sputtering system for S-i-a-Si:H layer deposition; this entirely different configuration minimized the c-Si surface damage by avoiding direct plasma exposure. In addition to this, efforts have also been made to passivate a c-Si surface by S-i-a-Si:H layers with a refinement in the plasma source itself (H 2 and Ar gas concentration variation) [10].…”
Section: Introductionmentioning
confidence: 99%